Quercetin and lithium chloride potentiate the protective effects of carvedilol against renal ischemia-reperfusion injury in high-fructose, high-fat diet-fed Swiss albino mice independent of renal lipid signaling. (5th January 2021) - Rezk, Asmaa M.; Ibrahim, Islam A.A.E.-H.; Mahmoud, Mona F.; Mahmoud, Amr A.A.
Abstract: Renal ischemia-reperfusion injury (R-IRI) is the main cause of acute renal failure. Carvedilol has been shown to protect against R-IRI. However, the underlying mechanisms are still not completely clarified. This study aimed to investigate the role of lipid signaling in mediating carvedilol protective effects against R-IRI in insulin-resistant mice by using two different lipid signaling modulators, quercetin and lithium chloride (LiCl). Mice were fed high-fructose, high-fat diet (HFrHFD) for 16 weeks to induce insulin resistance. At the end of feeding period, mice were randomly distributed into five groups; Sham, R-IRI, Carvedilol (20 mg/kg, i.p.), Carvedilol + Quercetin (10 mg/kg, i.p.), Carvedilol + LiCl (200 mg/kg, i.p.). R-IRI was performed by applying 30 min of unilateral renal ischemia followed by one hour of reperfusion. Quercetin and LiCl were administered 30 min before carvedilol administration and carvedilol was administered 30 min before ischemia. Changes in kidney function tests, histopathology, fibrosis area, lipid signaling, inflammatory, apoptosis and oxidative stress markers in the kidney were measured. Results showed that R-IRI decreased kidney function, impaired renal tissue integrity, modulated lipid signaling and increased renal inflammation, apoptosis and oxidative stress. Carvedilol treatment decreased the detrimental effects induced by R-IRI. In addition, pre-injection of both quercetin and LiCl potentiated the reno-protective effects of carvedilol against R-IRI independent of changes in lipid mediators like phosphatidyl inositol 4, 5 bisphosphate (PIP2) and diacylglycerol (DAG). In conclusion, quercetin and LiCl potentiate the protective effects of carvedilol against R-IRI in HFrHFD-fed mice by reducing inflammation and oxidative stress independent of lipid signaling. Highlights: Carvedilol protects against R-IRI in HFrHFD-fed mice. Quercetin potentiate the protective effects of carvedilol against R-IRI. LiCl potentiate the protective effects of carvedilol against R-IRI. Carvedilol reno-protective effects are not correlated with lipid signaling. The anti-inflammatory & antioxidant effects of carvedilol mediate reno-protection.